2006
DOI: 10.1002/bit.20902
|View full text |Cite
|
Sign up to set email alerts
|

Engineering aromaticL-amino acid transaminase for the asymmetric synthesis of constrained analogs ofL-phenylalanine

Abstract: An enzymatic asymmetric synthesis was carried out for the preparation of enantiomerically pure L-diphenylalanine using the rationally engineered aromatic L-amino acid transaminase (eAroATEs) obtained from Enterobacter sp. BK2K-1. To rationally redesign the enzyme, structural model was constructed by the homology modeling. The structural model was experimentally validated by the site-directed mutagenesis of the predicted pyridoxal-5'-phosphate (PLP) binding site and the substrate-recognition region, and the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…To select a template structure for the homology modeling, the primary structure of v-ATVf was compared with other aminotransferases using family profile analysis and sequence alignment (Eddy, 1998;Gribskov et al, 1987). The normalized log-odd score of v-ATVf calculated by the family profile of aminotransferase subgroup II (Cho et al, 2006;Mehta et al, 1993) showed a high positive value (profile score ¼ 194.4), whereas the values based on the family profiles of the other aminotransferase subgroups were negative values (profile score of subgroup I ¼ À197.2; profile score of subgroup III ¼ À198.6; profile score of subgroup IV ¼ À261.0). This result suggested that the v-ATVf is one of the aminotransferase subgroup II enzymes, whose members are ornithine aminotransferase (Orn-AT, EC 2.6.1.13), 4-aminobutyrate aminotransferase (GABA-AT, EC 2.6.1.19), DAPA aminotransferase (DAPA-AT, EC 2.6.1.62), glutamate-1-semialdehyde aminotransferase (GSA, EC 5.4.3.8), and 2,2-dialkylglycine decarboxylase (DGD, EC 4.1.1.64) (11,15,21,24).…”
Section: Resultsmentioning
confidence: 99%
“…To select a template structure for the homology modeling, the primary structure of v-ATVf was compared with other aminotransferases using family profile analysis and sequence alignment (Eddy, 1998;Gribskov et al, 1987). The normalized log-odd score of v-ATVf calculated by the family profile of aminotransferase subgroup II (Cho et al, 2006;Mehta et al, 1993) showed a high positive value (profile score ¼ 194.4), whereas the values based on the family profiles of the other aminotransferase subgroups were negative values (profile score of subgroup I ¼ À197.2; profile score of subgroup III ¼ À198.6; profile score of subgroup IV ¼ À261.0). This result suggested that the v-ATVf is one of the aminotransferase subgroup II enzymes, whose members are ornithine aminotransferase (Orn-AT, EC 2.6.1.13), 4-aminobutyrate aminotransferase (GABA-AT, EC 2.6.1.19), DAPA aminotransferase (DAPA-AT, EC 2.6.1.62), glutamate-1-semialdehyde aminotransferase (GSA, EC 5.4.3.8), and 2,2-dialkylglycine decarboxylase (DGD, EC 4.1.1.64) (11,15,21,24).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, transaminases allow asymmetric synthesis from prochiral ketone compounds depending upon the properties of target chemical compounds (1,4,10,11,17,49,50). Though transaminases are not widespread, we have reported an -transaminase of Alcaligenes denitrificans which can catalyze mainly the transamination between aliphatic ␤-amino acids and pyruvate (56).…”
mentioning
confidence: 99%
“…with unknown structure and no substrate specificity toward aromatic amino acid analogs was used to synthesize the l-phenylalanine analog l-diphenylalanine. Based on the interaction of the substrate with the active site of the enzyme, site-directed mutagenesis can alter the substrate specificity of the transaminase toward substrates with bulky side chains [118].…”
Section: Protein Engineering By Rational Enzyme Designmentioning
confidence: 99%